2020
DOI: 10.1186/s13033-020-00396-1
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience peer support programs for suicide prevention: a systematic scoping review

Abstract: Background: Peer-led support models have gained increasing popularity in suicide prevention. While previous reviews show positive effects of peer-led support for people with mental health problems and those bereaved by suicide, little is known about the types of lived experience peer support programs in suicide prevention and whether these are effective in improving the health and wellbeing of people at risk of suicide. The aim of this paper is to provide an overview of peer support programs that aim to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…[2][3][4] These newly minted mental health professionals were eventually integrated into a number of services in various mental healthcare settings, such as to support people with mental health conditions 5 , severe mental illnesses 4 6 and substance use issues. 7 Systematic reviews [8][9][10][11][12] supported these individual findings and demonstrated the effectiveness of integrating peer support workers into larger care teams. As a result of the benefit they bring to multidisciplinary care models, they have been integrated into community mental health teams 13 14 and supported employment teams 15 , where their presence is counted towards increased programme fidelity.…”
Section: Introductionmentioning
confidence: 84%
“…[2][3][4] These newly minted mental health professionals were eventually integrated into a number of services in various mental healthcare settings, such as to support people with mental health conditions 5 , severe mental illnesses 4 6 and substance use issues. 7 Systematic reviews [8][9][10][11][12] supported these individual findings and demonstrated the effectiveness of integrating peer support workers into larger care teams. As a result of the benefit they bring to multidisciplinary care models, they have been integrated into community mental health teams 13 14 and supported employment teams 15 , where their presence is counted towards increased programme fidelity.…”
Section: Introductionmentioning
confidence: 84%
“…The strong representation of people with lived experience of suicide in the network membership and among network coordinators reflects another unique characteristic of community coalition in the suicide prevention field. The value of lived experience expertise has been increasingly recognised as pivotal to the design and delivery of suicide prevention programs [ 25 , 26 ], and it is evident that LifeForce networks provide an effective means for engaging community members with a lived experience in suicide prevention. Notwithstanding some of these unique features, LifeForce networks also shared many characteristics of community coalitions in the broader health promotion field.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the results, four of these participants reported volunteering or working in formal peer-support, in addition to most having utilized either formal or informal peer-support. The research on the effectiveness of peer-support for suicide prevention is surprisingly limited, given the increasing popularity of peer-support [25]. A systematic scoping review by Schlichthorst et al (2020) [25] yielded seven records of eight suicide prevention peer-support programs, and only three of those had evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the effectiveness of peer-support for suicide prevention is surprisingly limited, given the increasing popularity of peer-support [25]. A systematic scoping review by Schlichthorst et al (2020) [25] yielded seven records of eight suicide prevention peer-support programs, and only three of those had evaluations. The authors of the review concluded that, while peer-support programs for suicide prevention show promise, there needs to be better evaluation [25].…”
Section: Discussionmentioning
confidence: 99%